2021
DOI: 10.1007/s12403-021-00412-w
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Toxic Metals in Children Exposed to Urban Pollution and to Cement Plant Emissions

Abstract: Cement plants located in urban areas can increase health risk. Although children are particularly vulnerable, biomonitoring studies are lacking. Toenail concentration of 24 metals was measured in 366 children (6-10 years), who live and attend school in a city hosting a cement plant. Living addresses and schools were geocoded and attributed to exposed or control areas, according to modeled ground concentrations of PM 10 generated by the cement plant. Air levels of PM 10 and NO 2 were monitored. PM 10 levels wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 135 publications
0
4
0
1
Order By: Relevance
“…33 MC-LR and Cd coexist widely in the aquatic ecosystem with the aggravation of environmental pollution and the continuous discharge of industrial, agricultural, and domestic sewage. 14,15 However, to our knowledge, there is no report on the negative effects of MC-LR combined with Cd exposure on humans. We observed a positive additive interaction between MC-LR and Cd exposures in humans, which indicates that MC-LR combined with Cd synergistically increases the CKD risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33 MC-LR and Cd coexist widely in the aquatic ecosystem with the aggravation of environmental pollution and the continuous discharge of industrial, agricultural, and domestic sewage. 14,15 However, to our knowledge, there is no report on the negative effects of MC-LR combined with Cd exposure on humans. We observed a positive additive interaction between MC-LR and Cd exposures in humans, which indicates that MC-LR combined with Cd synergistically increases the CKD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic exposure to Cd is associated with a reduced glomerular filtration rate (GFR), causing kidney damage. , Previous studies also indicate that Cd in blood, urine, or diet can increase CKD risk. , However, multiple sources of exposure often occur simultaneously in the environment. Studies have shown that Cd and cyanobacterial blooms widely coexist in aquatic ecosystems. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is surrounded by a residential area and extends along the Adriatic coast in a south–east direction for 7 km, close to the coast. In support of these considerations regarding the critical qualities of the study area, a recent study by Di Ciaula [ 31 ] demonstrated the bioaccumulation of Hg, Ni, Cd and As in children living nearby.…”
Section: Study Areamentioning
confidence: 87%
“…Кадмий и свинец относятся к числу металлов первого класса токсичности. Их широкое распространение в окружающей среде объясняется выбросами от сжигания жидкого и твердого топлива [2,3], бытовых отходов [4], от продуктов износа автомобильного транспорта [5], строительных и электробытовых материалов [6,7]. Указанные источники выбросов кадмия и свинца универсальны как для больших, так и для малых городов, поэтому необходима локальная оценка их присутствия в окружающей среде всех субъектов Российской Федерации.…”
Section: Introductionunclassified